2023
DOI: 10.24875/gmm.m20000430
|View full text |Cite
|
Sign up to set email alerts
|

Study of the cytotoxic and irritant effects of skin cleansing soaps

Abstract: Introducción: El jabón para el aseo cutáneo es de empleo común entre la población, sin embargo, es posible que cause daño a las células de la piel y modifique la barrera cutánea. Objetivo: Determinar el efecto citotóxico de los jabones en queratinocitos cultivados in vitro y correlacionarlo con la irritación clínica. Método: Se realizó una encuesta para conocer los jabones comerciales más utilizados y su cantidad; posteriormente, se evaluó su citotoxicidad en cultivos de queratinocitos humanos mediante el méto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…48 h treatment of HaCat cells of LS I caused significant cytotoxicity in a range above 0.5%. This is in line with previous research in which a high concentration of soaps or other care products significantly reduces cell number after a short [ 36 , 37 ] and long exposition [ 38 ]. Both Cocamidopropyl Betaine (LS II) and CocamidopropylHydroxysultaine (LS III) did not affect the cytotoxic properties of LS I.…”
Section: Discussionsupporting
confidence: 92%
“…48 h treatment of HaCat cells of LS I caused significant cytotoxicity in a range above 0.5%. This is in line with previous research in which a high concentration of soaps or other care products significantly reduces cell number after a short [ 36 , 37 ] and long exposition [ 38 ]. Both Cocamidopropyl Betaine (LS II) and CocamidopropylHydroxysultaine (LS III) did not affect the cytotoxic properties of LS I.…”
Section: Discussionsupporting
confidence: 92%
“…We used TWEL and visual erythema scores to assess skin irritation, as they have been extensively utilized in several studies for this purpose. [19][20][21][22][23][24] This study demonstrated that ES makes the skin more sensitive to irritating stimuli such as SLS, even at concentrations as low as 0.5%. Even more so, with higher concentrations of SLS (5%) com-TA B L E 1 Transepidermal water loss (TWEL) mean values after 24 h of patch removal for areas 1, 2, 3, and 4 on the experimental and control forearms.…”
Section: Discussionmentioning
confidence: 59%
“…We used TWEL and visual erythema scores to assess skin irritation, as they have been extensively utilized in several studies for this purpose 19–24 . This study demonstrated that ES makes the skin more sensitive to irritating stimuli such as SLS, even at concentrations as low as 0.5%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations